204k views
0 votes
Please help fast!!!!

Evaluate the expression when a = 6, b = 3 and c = 2:
c(b + a ) – a = ______

2 Answers

5 votes

So the right answer is 12.

look at the attached picture

hope it helps

Please help fast!!!! Evaluate the expression when a = 6, b = 3 and c = 2: c(b + a-example-1
User Birophilo
by
5.5k points
5 votes

Answer:

12

Explanation:

We have the expression:

c(b+a)-a

We know that a is equal to 6, b is equal to 3, and c is equal to 2. Therefore, we can substitute 6 in for a, 3 in for b, and 2 in for c.

2(3+6)-6

Now, solve according to PEMDAS (Parentheses, Exponents, Multiplication, Division, Addition, Subtraction)

First, solve inside of the parentheses. Add 3 and 6.

2(9)-6

Next, multiply 2 and 9.

18-6

Subtract 6 from 18

12

User Muhammedogz
by
6.7k points